2003
DOI: 10.1177/104990910302000309
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers’ satisfaction with hospice care in the last 24 hours of life

Abstract: The goals of this study were to identify elements of care that contributed to positive and negative perceptions of hospice care in the last 24 hours of life, and to define patient and family characteristics that are associated with satisfaction with care during this difficult period. Surveys were sent to 207 primary caregivers, and 112 surveys were returned. This study reports four findings that elucidate the factors that make family members more or less satisfied with the care that their loved one received du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
2
15
1
Order By: Relevance
“…He wasn't real familiar with it and he was just so sick, he just took it, somebody to help me when I go Downloaded by [Simon Fraser University] at 08:01 17 November 2014 home, you know?" This sentiment was similar to other studies' findings that patients and families only found out about the most beneficial aspects of hospice after enrollment (Casarett et al, 2004;Casarett et al, 2003).…”
Section: Understanding Of Hospicesupporting
confidence: 91%
See 1 more Smart Citation
“…He wasn't real familiar with it and he was just so sick, he just took it, somebody to help me when I go Downloaded by [Simon Fraser University] at 08:01 17 November 2014 home, you know?" This sentiment was similar to other studies' findings that patients and families only found out about the most beneficial aspects of hospice after enrollment (Casarett et al, 2004;Casarett et al, 2003).…”
Section: Understanding Of Hospicesupporting
confidence: 91%
“…The median length of service was 20 days, down from 20.6 in 2006 (NHPCO, 2008). Recent studies have reported that families receiving hospice services had lower rates of unmet needs, in particular, emotional needs (Teno et al, 2004), and were satisfied with the level of care provided (Casarett, Hirschman, Crowley, Galbraith, & Leo, 2003;Rhodes, Mitchell, Miller, Connor, & Teno, 2008;Teno et al, 2004). It is now widely accepted that hospice services can improve the multidimensional symptoms often present at the end of life; however, the proportion of individuals near the end of life that would ideally benefit from hospices services or what the optimal length of care is in general is still unknown (Casarett & Quill, 2007).…”
mentioning
confidence: 95%
“…Two studies that have used cognitive interviews have explored how bereaved respondents answer questions in retrospective surveys; they found that respondents were drawing on memories of the deceased and not just their own feelings in answering questions 67 68. Other researchers have found that bereavement respondents’ feelings of distress were not related to their satisfaction scores,69 or that both respondent characteristics and characteristics of services determined satisfaction 70. The current evidence therefore discounts the possibility that retrospective surveys only reflect bereavement distress.…”
Section: Discussioncontrasting
confidence: 60%
“…According to primary caregivers as well, patients' life quality increased after hospice services were implemented (McMillan and Mahon 1994). Previous studies also indicate that family members are very satisfied with hospice care, especially when compared to the care offered by other institutions (Ringdal et al 2002;Casarett et al 2003;Teno et al 2004). Studies conducted in an Australian hospice showed that there was a relationship between satisfaction with hospice care and quality of life.…”
Section: Introductionmentioning
confidence: 99%